Parental alienation among families in north-east Mexico. New challenges for social work - Alemán, Jesús Acevedo (Cuadernos de Trabajo Social, 2020)
Parental alienation syndrome (PAS) has been interpreted as behaviour involving children showing disrespect or hostility toward their parents, resulting from the malicious influence of one of their parents or even of third parties. It is a process in which minors’ minds are manipulated in order for them to repeat untruths, fanciful stories and descriptions of non-existent abuse or mistreatment created by the parent or whoever is guiding the minor. It is recognised today that parental alienation does not only arise in processes involving litigation or legal disputes over child custody; it also presents itself in the context of everyday family dynamics. In this regard, the aim of this article is to identify the presence of alienating practices among 150 families from 12 neighbourhoods in Ciudad de Saltillo, Coahuila, México. The conclusion is that parental alienation is present among the families studied, even though none of them are involved in processes of separation or litigation over child custody. This means that there does not necessarily have to be a formal separation process in order for parental alienation or its impacts to be present.